Material for coating scraper and preparation method thereof

Through the Al0.6CrFeNi2.4Moe multi-component alloy system, the Mo content is adjusted to form a cast alloy with high strength, plasticity and corrosion resistance, which solves the shortcomings of existing coating scraper materials in terms of strength, corrosion resistance and brittleness, and reduces production costs.

CN119824278APending Publication Date: 2025-04-15JIANGSU UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510042927.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing coating scraper materials have shortcomings in terms of high strength, corrosion resistance and brittleness, and require complex heat treatment processes, which are costly.

Method used

The Al0.6CrFeNi2.4Moe multi-component alloy system is adopted to form a cast alloy with high strength, plasticity and corrosion resistance by adjusting the Mo content, avoiding the heat treatment step.

Benefits of technology

The high yield strength, excellent plasticity and good corrosion resistance of coated scraper materials are achieved, which reduces production costs and adapts to the coating needs of different coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824278A_ABST
    Figure CN119824278A_ABST
Patent Text Reader

Abstract

The invention relates to a material for a coating scraper and a preparation method of the material, and belongs to the technical field of coating scraper materials. The structural formula of the material for the coating scraper is AlaCrbFecNidMoe, wherein the ratio of a to b to c to d to e is (0.5 to 0.8) to (0.8 to 1.2) to (0.8 to 1.2) to (2.0 to 3.0) to (0.2 to 0.8). According to the Al-Cr-Fe-Ni-Mo multi-component alloy system provided by the invention, the optimal combination of strength, plasticity and corrosion resistance is achieved by adjusting the Mo content, so that the coating requirements of different coatings are met; on the basis that high corrosion resistance of an existing scraper material is kept, the material has obvious advantages in main mechanical performance indexes such as yield strength and plasticity compared with the existing material, and the obtained material is in an as-cast state and does not need heat treatment, so that a large amount of cost of heat treatment is saved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of coating scraper materials, and in particular to a coating scraper material and a preparation method thereof. Background Art

[0002] The coating equipment is prone to uneven coating during operation, which requires a coating scraper to scrape the coating evenly. The coating scraper is a special mechanical blade used on the coating machine to apply a layer of glue, paint or ink with specific functions. It is widely used in the coating preparation of thermal paper, cloth, leather, aluminum foil, plastic film and other materials. During the coating process, the scraper needs to have good strength, plasticity and corrosion resistance. Common coating scraper materials include: stainless steel (such as 304, 316 stainless steel), titanium alloy (such as Ti-6Al-4V), cemented carbide (WC-Co alloy), etc. Stainless steel can resist the erosion of corrosive substances such as acid, alkali and water, and is particularly suitable for use in wet environments, but the strength is not high, and it is mostly used in wet coating, ink coating and other processes. Ti-6Al-4V has good strength and corrosion resistance, and is lighter than stainless steel. It is usually used in coating processes in high-precision and high-corrosion environments. WC-Co alloy is a composite material composed of tungsten and cobalt. It has very high hardness, strength and good corrosion resistance, but it is also very brittle. The performance guarantee of the three alloys requires a complex heat treatment process, which is expensive. Therefore, the development of a coating scraper material that can meet the requirements of high strength, corrosion resistance and low brittleness without heat treatment has great application potential in the coating scraper field.

[0003] The traditional alloy system is mainly based on an element with some special properties, and a small amount of other elements is added to improve its performance. The types of commonly used metal elements are limited, and the amount of addition is also limited, which invisibly restricts the amount of coating scraper materials that can be used. The concept of multi-component alloys (high entropy alloys) breaks this limitation. The number of main elements is ≥5, and its high entropy effect can inhibit the formation of brittle metal compounds between the elements, thereby forming a solid solution with a simple face-centered cubic, body-centered cubic and other structures. For example, the FCC structure of Al 0.6 CrFeNi 2.4 The alloy exhibits excellent plasticity and corrosion resistance. Studies have shown that, based on a multi-component alloy system, increasing or changing the content of one element can significantly change the microstructure of the alloy and thus improve its performance. Studies have shown that in the FCC phase of CoCrFeNi, CoCrFeMnNi and Al 0.5Adding Mo element to CoCrFeNi alloy can improve the strength and hardness of the alloy through solid solution strengthening and reduce the wear rate of the alloy. Mo element is beneficial to promote the precipitation of Cr-Mo-rich hard and brittle σ phase and μ phase in FCC phase. Proper control of Mo content can improve the strength of the alloy without reducing plasticity. The role of Mo element in stainless steel has been fully studied, and studies have shown that Mo can improve the corrosion resistance of the alloy in NaCl solution. Summary of the invention

[0004] In view of this, the present application provides a coating scraper material and a preparation method thereof. The coating scraper material has ultra-high strength and plasticity, and at the same time has excellent corrosion resistance in a simulated coating corrosion environment. As an alloy for a coating scraper, compared with existing coating scraper materials, the comprehensive performance is greatly improved, and it can effectively overcome the defects of the above-mentioned prior art.

[0005] The first aspect of the present application provides a coating blade material, the structural formula of the coating blade material is Al a Cr b Fe c Ni d Mo e , where the ratios of a:b:c:d:e are (0.5-0.8):(0.8-1.2):(0.8-1.2):(2.0-3.0):(0.2-0.8).

[0006] Preferably, the value of a is 0.6, the value of b is 1, the value of c is 1, the value of d is 2.4, and the value of e is 0.2, 0.4, 0.6 or 0.8.

[0007] Specifically, the structural formula of the coating blade material is Al 0.6 CrFeNi 2.4 Mo 0.2 、Al 0.6 CrFeNi 2.4 Mo 0.4 、Al 0.6 CrFeNi 2.4 Mo 0.6 or Al 0.6 CrFeNi 2.4 Mo 0.8 .

[0008] The second aspect of the present application also provides a method for preparing the above-mentioned coating blade material, comprising the following steps:

[0009] (1) placing alloy raw materials composed of metals Al, Cr, Fe, Ni, and Mo and a titanium sponge block into two crucibles in a non-consumable vacuum arc melting furnace, and melting the titanium sponge block under argon protection after evacuation, wherein the titanium sponge block is used to absorb residual oxygen in the environment;

[0010] (2) arc melting the alloy raw material under argon protection, accompanied by electromagnetic stirring during the arc melting process, and obtaining a button sample after cooling;

[0011] (3) The cooled button sample is taken out from the arc melting furnace, the surface oxide layer is removed, and the button sample is reloaded into the arc melting furnace for suction casting to obtain a coating scraper material.

[0012] Preferably, the step (1) is specifically as follows: pre-treating the alloy raw material and the titanium sponge block respectively; placing the pre-treated alloy raw material and the titanium sponge block respectively into two crucibles in a non-consumable vacuum arc melting furnace, and evacuating to 2.5×10 -3 After reaching 0.5-10 Pa, the argon valve is opened to restore the pressure in the furnace chamber to 0.5-10 Pa, and the sponge titanium block is first melted under the protection of argon to remove residual oxygen in the smelting environment and prevent oxidation of the metal during the smelting process.

[0013] Preferably, the specific process of the pretreatment is: grinding the alloy raw material and the titanium sponge block with an angle grinder, a grinding wheel or sandpaper, and then using alcohol or acetone as a cleaning solvent to oscillate and clean the alloy raw material and the titanium sponge block in an ultrasonic wave for 5 to 10 minutes, and the power density of the ultrasonic wave is 0.5 to 1.5 W / cm 2 , frequency is 25~55Hz.

[0014] Specifically, the purity of each metal element such as Al, Cr, Fe, Ni, Mo, etc. is ≥99.9wt.%.

[0015] Preferably, the step (2) is specifically as follows: arc melting the alloy raw material under argon protection, the arc melting current is 50-100A, and the arc melting process is accompanied by electromagnetic stirring, and a button sample is obtained after cooling; the arc melting process is repeated multiple times on the button sample to ensure that the alloy raw material is completely melted and the composition is uniform.

[0016] Preferably, the button sample is turned over before repeating the arc melting process each time, and the melting time needs to be maintained at 2 to 5 minutes during the repeated arc melting process.

[0017] Preferably, the step (3) is specifically as follows: taking out the cooled button sample from the arc melting furnace, removing the surface oxide layer of the button sample, and reloading it into the arc melting furnace for suction casting treatment at a suction casting pressure of 1 to 10 Pa to obtain a coating scraper material.

[0018] Specifically, the cooled button samples are taken out from the arc melting furnace, cut into small pieces, and the surface oxide layer of the small pieces is removed. The small pieces are then put back into the arc melting furnace, and alloy samples of different sizes are obtained after melting, suction casting and cooling.

[0019] Preferably, the specific process of removing the surface oxide layer of the button sample is: grinding the button sample with an angle grinder, a grinding wheel machine or sandpaper, and then using alcohol or acetone as a cleaning solvent to oscillate and clean the button sample in an ultrasonic wave for 5 to 10 minutes, and the power density of the ultrasonic wave is 0.5 to 1.5 W / cm 2 , frequency is 25~55Hz.

[0020] Compared with the prior art, this application has the following beneficial effects:

[0021] 1. The Al-Cr-Fe-Ni-Mo multi-component alloy system provided in the present application achieves the best combination of strength, plasticity and corrosion resistance by adjusting the Mo content to meet the coating requirements of different coatings; its performance maintains the high corrosion resistance of existing scraper materials, and at the same time has obvious advantages over existing materials in major mechanical properties such as yield strength and plasticity, and the obtained material is in a cast state and does not require heat treatment, saving a lot of heat treatment costs.

[0022] 2. The coating scraper material provided in the present application has a single-phase solid solution structure and high plasticity when the Mo content is low. As the Mo content increases, a harder intermetallic compound σ phase gradually precipitates in the alloy, and the strength of the alloy is improved. 0.6 CrFeNi 2.4 Mo 0.8 The multi-component alloy has a two-phase structure of FCC+σ in the cast state, a yield strength of 1504MPa, an elongation of 21.4%, and has ultra-high combined strength and plasticity. Its corrosion resistance in the corrosive environment of 3.5% NaCl solution is comparable to that of stainless steel. Compared with the existing coating scraper materials, while retaining high corrosion resistance, both strength and plasticity have been greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions in the present application or the prior art, the drawings required for use in the description of the present application or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0024] Figure 1 XRD patterns of the Al-Cr-Fe-Ni-Mo quinary alloy system prepared in Examples 1-4 and the multi-component alloy in Comparative Example 1, wherein Figure 1 (a) is the overall view from 20° to 90°. Figure 1 (b) is a local enlarged view from 39° to 47°. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solutions and advantages of this application clearer, the technical solutions in this application will be clearly and completely described below in conjunction with the drawings in this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0026] Unless otherwise specifically stated, the numerical value set forth in these embodiments does not limit the scope of the application. The technology and method known to those of ordinary skill in the relevant art may not be discussed in detail, but in appropriate cases, the technology and method should be considered as a part of the specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values.

[0027] Unless otherwise specified, the experimental methods used in the examples of this application are all conventional methods.

[0028] In the following examples and comparative examples, unless otherwise specified, all raw materials can be obtained by commercial purchase or conventional methods.

[0029] It should be noted that the following embodiment provides a high-strength-plastic-corrosion-resistant multi-component coating scraper material for coating scrapers, and its composition is Al 0.6 CrFeNi 2.4 Mo e , where e is 0.2, 0.4, 0.6 and 0.8 respectively. The atomic percentage can be converted to atomic percentage by performing corresponding calculations. For example, when e=0.2, the atomic percentage of Mo is (0.2 / 5.2)*100%.

[0030] Example 1

[0031] A high-strength-plastic-corrosion-resistant multi-component coating scraper material for a coating scraper, comprising metal raw materials of the following atomic ratios: Al0.6, Cr 1, Fe 1, Ni 2.4, Mo 0.2, expressed as Al 0.6 CrFeNi 2.4 Mo 0.2 Multi-component alloy, referred to as Mo0.2.

[0032] The preparation method of the above Mo0.2 multi-component alloy is as follows:

[0033] (1) The metal raw materials Al, Cr, Fe, Ni, Mo and sponge titanium blocks were prepared according to the ratio, and the raw materials and sponge titanium blocks were polished with a grinder to remove surface impurities and oxides. The purity of each metal raw material was higher than 99.9wt.%. After polishing, acetone was used as a cleaning solvent. The power density was 0.8W / cm 2 and oscillate and clean in an ultrasonic cleaning machine at a frequency of 33 Hz for 5 minutes, and then dry;

[0034] (2) The titanium sponge block and the metal raw materials Al, Cr, Fe, Ni, and Mo prepared according to the ratio are respectively placed in two different crucibles in a non-consumable vacuum arc melting furnace, and the vacuum is evacuated to 2.5×10 -3 Pa, then backfill with argon to 5Pa. Under the protection of argon, first melt the titanium sponge block for 1min, and then melt the weighed metal raw materials in another crucible at a current of 60A. The arc melting process is accompanied by electromagnetic stirring to increase the uniformity of alloy mixing. To ensure the uniform chemical composition of the alloy ingot, each metal ingot is turned over 5 times, each melting time is 60s, a total of 5min, to obtain a button sample;

[0035] (3) Take out the button sample and remove its surface oxide layer (grind the button sample with an angle grinder, a grinding wheel machine or sandpaper, and then use alcohol or acetone as a cleaning solvent to oscillate and clean the button sample in an ultrasonic wave for 5 minutes, and the power density of the ultrasonic wave is 1.2 W / cm 2 , frequency is 33 Hz), and Mo0.2 multi-component alloy rods are obtained by suction casting at a pressure of 5 Pa.

[0036] Example 2

[0037] A high-strength-plastic-corrosion-resistant multi-component coating scraper material for a coating scraper, comprising the following metal raw materials in atomic ratio: Al0.6, Cr 1, Fe 1, Ni 2.4, Mo 0.4, expressed as Al 0.6 CrFeNi 2.4 Mo 0.4 Multi-component alloy, referred to as Mo0.4.

[0038] The preparation method of the above Mo0.4 multi-component alloy is as follows:

[0039] (1) The metal raw materials Al, Cr, Fe, Ni, Mo and sponge titanium blocks were prepared according to the ratio, and the raw materials and sponge titanium blocks were polished with a grinder to remove surface impurities and oxides. The purity of each metal raw material was higher than 99.9wt.%. After polishing, acetone was used as a cleaning solvent. The power density was 0.8W / cm 2 and oscillate and clean in an ultrasonic cleaning machine at a frequency of 33 Hz for 8 minutes, and then dry;

[0040] (2) The titanium sponge block and the metal raw materials Al, Cr, Fe, Ni, and Mo prepared according to the ratio are respectively placed in two different crucibles in a non-consumable vacuum arc melting furnace, and the vacuum is evacuated to 2.5×10 -3 Pa, then backfill with argon to 1Pa. Under the protection of argon, first melt the titanium sponge block for 1min, and then melt the weighed metal raw materials in another crucible at a current of 70A. The arc melting process is accompanied by electromagnetic stirring to increase the uniformity of alloy mixing. To ensure the uniform chemical composition of the alloy ingot, each metal ingot is turned over 6 times, each melting time is 40s, a total of 4min, to obtain a button sample;

[0041] (3) Take out the button sample and remove its surface oxide layer (grind the button sample with an angle grinder, a grinding wheel machine or sandpaper, and then use alcohol or acetone as a cleaning solvent to oscillate and clean the button sample in an ultrasonic wave for 8 minutes, and the power density of the ultrasonic wave is 1.2 W / cm 2 , frequency is 33 Hz), and Mo0.4 multi-component alloy rods are obtained by suction casting at a pressure of 5 Pa.

[0042] Example 3

[0043] A high-strength-plastic-corrosion-resistant multi-component coating scraper material for a coating scraper, comprising the following metal raw materials in atomic ratio: Al0.6, Cr 1, Fe 1, Ni 2.4, Mo 0.6, expressed as Al 0.6 CrFeNi 2.4 Mo 0.6 Multi-component alloy, referred to as Mo0.6.

[0044] The preparation method of the above Mo0.6 multi-component alloy is as follows:

[0045] (1) The metal raw materials Al, Cr, Fe, Ni, Mo and sponge titanium blocks were prepared according to the ratio, and the raw materials and sponge titanium blocks were polished with a grinder to remove surface impurities and oxides. The purity of each metal raw material was higher than 99.9wt.%. After polishing, acetone was used as a cleaning solvent. The power density was 0.8W / cm 2 and oscillate and clean in an ultrasonic cleaning machine at a frequency of 33 Hz for 5 minutes, and then dry;

[0046] (2) The titanium sponge block and the metal raw materials Al, Cr, Fe, Ni, and Mo prepared according to the ratio are respectively placed in two different crucibles in a non-consumable vacuum arc melting furnace, and the vacuum is evacuated to 2.5×10 -3 Pa, then backfill with argon to 5Pa. Under the protection of argon, first melt the titanium sponge block for 1min, and then melt the weighed metal raw materials in another crucible at a current of 80A. The arc melting process is accompanied by electromagnetic stirring to increase the uniformity of alloy mixing. To ensure the uniform chemical composition of the alloy ingot, each metal ingot is turned over 5 times, each melting time is 60s, a total of 5min, to obtain a button sample;

[0047] (3) Take out the button sample and remove its surface oxide layer (grind the button sample with an angle grinder, a grinding wheel machine or sandpaper, and then use alcohol or acetone as a cleaning solvent to oscillate and clean the button sample in an ultrasonic wave for 10 minutes, and the power density of the ultrasonic wave is 1.2 W / cm 2 , frequency is 50 Hz), and Mo0.6 multi-component alloy rods are obtained by suction casting under a pressure of 5 Pa.

[0048] Example 4

[0049] A high-strength-plastic-corrosion-resistant multi-component coating scraper material for a coating scraper, comprising the following metal raw materials in atomic ratio: Al0.6, Cr 1, Fe 1, Ni 2.4, Mo 0.8, expressed as Al 0.6 CrFeNi 2.4 Mo 0.8 Multi-component alloy, referred to as Mo0.8.

[0050] The preparation method of the above Mo0.8 multi-component alloy is as follows:

[0051] (1) The metal raw materials Al, Cr, Fe, Ni, Mo and sponge titanium blocks were prepared according to the ratio, and the raw materials and sponge titanium blocks were polished with a grinder to remove surface impurities and oxides. The purity of each metal raw material was higher than 99.9wt.%. After polishing, acetone was used as a cleaning solvent. The power density was 0.8W / cm 2 and oscillate and clean in an ultrasonic cleaning machine at a frequency of 33 Hz for 5 minutes, and then dry;

[0052] (2) The titanium sponge block and the metal raw materials Al, Cr, Fe, Ni, and Mo prepared according to the ratio are respectively placed in two different crucibles in a non-consumable vacuum arc melting furnace, and the vacuum is evacuated to 2.5×10 -3 Pa, then backfill with argon to 5Pa. Under the protection of argon, first melt the titanium sponge block for 1min, and then melt the weighed metal raw materials in another crucible at a current of 60A. The arc melting process is accompanied by electromagnetic stirring to increase the uniformity of alloy mixing. To ensure the uniform chemical composition of the alloy ingot, each metal ingot is turned over 6 times, each melting time is 50s, a total of 5min, to obtain a button sample;

[0053] (3) Take out the button sample and remove its surface oxide layer (grind the button sample with an angle grinder, a grinding wheel machine or sandpaper, and then use alcohol or acetone as a cleaning solvent to oscillate and clean the button sample in an ultrasonic wave for 10 minutes, and the power density of the ultrasonic wave is 1.5 W / cm 2 , frequency is 50 Hz), and Mo0.8 multi-component alloy rods are obtained by suction casting at a pressure of 5 Pa.

[0054] Comparative Example 1

[0055] The multi-component alloy composition provided in this comparative example adopts Al without Mo. 0.6 CrFeNi 2.4 The alloy is referred to as Mo0. Its preparation process is consistent with that of Example 1.

[0056] Test Case

[0057] 1. X-ray diffractometer was used to analyze the Al 0.6 CrFeNi 2.4 Mo e (e=0.2, 0.4, 0.6, 0.8) and comparative example 1 were subjected to phase analysis, the operating voltage and current were 40KV and 20mA respectively, the X-ray source was CuKα (λ=0.1542nm) ray, and the scanning angle 2θ ranged from 20 to 120°.

[0058] The XRD spectra of the alloys of Examples 1 to 4 and Comparative Example 1 are as follows: Figure 1 As shown by Figure 1 It can be seen that the phase structure of alloys with different Mo contents changes. Comparative Example 1 and Example 1 are both single-phase FCC solid solutions. With the increase of Mo content, the peak of the σ phase is significantly enhanced, which indicates an increase in the volume fraction of the σ phase, proving that the addition of Mo element promotes the formation of the σ phase.

[0059] 2. Three common alloys for coating scrapers, 316 stainless steel, Ti-6Al-4V, and WC-Co alloy, were selected as Comparative Example 2, Comparative Example 3, and Comparative Example 4, respectively. Compression performance and corrosion resistance tests were performed on Examples 1 to 4 and Comparative Examples 1 to 4. The test data are shown in Table 1.

[0060] Compression performance test method: The diameter of the cylindrical specimen used for the compression test is 4 mm and the height is 6 mm. The axis of the specimen is parallel to the outer surface of the cylinder, and the upper and lower planes are parallel. The compression test is carried out at room temperature using a computer-controlled high-temperature electronic universal testing machine. Apply 5.6×10 -3 A constant compression speed of mm / s corresponds to 10 -3 s -1 The initial strain rate.

[0061] Corrosion resistance test method: The alloy performance test adopts a three-electrode system, with a cold-mounted sample as the working electrode, a platinum sheet as the auxiliary electrode, a silver chloride electrode as the reference electrode, and a 3.5wt.% NaCl solution as the corrosion solution. The polarization curve was measured using a CHI760E electrochemical workstation to obtain the self-corrosion current and self-corrosion voltage of the alloy. The scanning range of the polarization curve is -1.5V to 1.5V, and the scanning rate is 0.01V.

[0062] Table 1 Performance data of embodiments and comparative examples

[0063]

[0064] It can be seen from Table 1 that:

[0065] Strong plasticity: The yield strength of Examples 1-4 is better than that of Comparative Examples 1 and 2. As the Mo content increases, the yield strength of Example 4 exceeds that of Comparative Example 3 and is comparable to Comparative Example 4, which is known for its strength and hardness. In the case of low Mo content, Examples 1 and 2 have an excellent plasticity of more than 60%. With the further addition of Mo element, the yield strength of Examples 3 and 4 is significantly improved, and still has good plasticity. The yield strength and plasticity of Example 4 reach 1504MPa and 21.4% respectively, and have excellent mechanical properties of strength-plasticity.

[0066] Corrosion resistance: It is generally believed that a higher self-corrosion voltage represents an alloy that is more difficult to corrode and has better corrosion resistance, while the self-corrosion current represents the corrosion rate of the alloy after corrosion starts. The electrochemical parameters of the example in 3.5wt.% NaCl solution are close to those of the stainless steel in comparative example 2, and have better corrosion resistance.

[0067] With the difference in the content of an element, there are differences in the phase structure of the multi-component alloy, which ultimately leads to differences in performance. By adding different Mo contents, it is reasonable to infer that the content of the Mo element can be adjusted to achieve the best combination of strength-plasticity-corrosion resistance to meet the needs of different coating environments. Its performance maintains the high corrosion resistance of existing materials, and at the same time has obvious advantages over existing materials in terms of major mechanical properties such as yield strength and elongation. The material described in this application is in a cast state and does not require heat treatment, saving a lot of heat treatment costs.

[0068] The present application provides a high-strength-plastic-corrosion-resistant multi-component coating scraper material for coating scrapers, which provides useful inspiration on how to control the generated phase by changing the alloy elements, thereby improving and regulating the alloy properties; in addition, the preparation method of the present application is simple and reliable, the selected elements are non-toxic and easy to obtain, the comprehensive performance of the alloy has obvious advantages over many existing materials, and it has good economy and high application value.

[0069] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A coating blade material, characterized in that: The structural formula of the coating blade material is Al a Cr b Fe c Ni d Mo e , where the ratios of a:b:c:d:e are (0.5-0.8):(0.8-1.2):(0.8-1.2):(2.0-3.0):(0.2-0.8).

2. The coating blade material according to claim 1, characterized in that: The value of a is 0.6, the value of b is 1, the value of c is 1, the value of d is 2.4, and the value of e is 0.2, 0.4, 0.6 or 0.

8.

3. A method for preparing a coating blade material according to claim 1 or 2, characterized in that: The following steps are involved: (1) placing alloy raw materials composed of metals Al, Cr, Fe, Ni, and Mo and a titanium sponge block into two crucibles in a non-consumable vacuum arc melting furnace, and melting the titanium sponge block under argon protection after evacuation; (2) arc melting the alloy raw material under argon protection, accompanied by electromagnetic stirring during the arc melting process, and obtaining a button sample after cooling; (3) The cooled button sample is taken out from the arc melting furnace, the surface oxide layer is removed, and the button sample is reloaded into the arc melting furnace for suction casting to obtain a coating scraper material.

4. The method for preparing the coating blade material according to claim 3, characterized in that: The step (1) specifically comprises: pre-treating the alloy raw material and the titanium sponge block respectively; placing the pre-treated alloy raw material and the titanium sponge block respectively into two crucibles in a non-consumable vacuum arc melting furnace, and evacuating the furnace to a vacuum of 2.5×10 -3 After reaching 0.5-10 Pa, the argon valve is opened to restore the pressure in the furnace chamber to 0.5-10 Pa, and the sponge titanium block is first melted under the protection of argon.

5. The method for preparing the coating blade material according to claim 4, characterized in that: The specific process of the pretreatment is: using an angle grinder, a grinding wheel machine or sandpaper to grind the alloy raw material and the sponge titanium block, and then using alcohol or acetone as a cleaning solvent to oscillate and clean the alloy raw material and the sponge titanium block in an ultrasonic wave for 5 to 10 minutes, and the power density of the ultrasonic wave is 0.5 to 1.5 W / cm 2 , frequency is 25~55Hz.

6. The method for preparing the coating blade material according to claim 3, characterized in that: The step (2) specifically comprises: arc melting the alloy raw material under argon protection, the arc melting current being 50-100A, and the arc melting process being accompanied by electromagnetic stirring, and obtaining a button sample after cooling; repeating the arc melting process for multiple times on the button sample to ensure that the alloy raw material is completely melted and has a uniform composition.

7. The method for preparing the coating blade material according to claim 6, characterized in that: The button sample is turned over before repeating the arc melting process each time, and the melting time needs to be kept at 2 to 5 minutes during the repeated arc melting process.

8. The method for preparing a coating blade material according to claim 3, characterized in that: The step (3) is specifically as follows: taking out the cooled button sample from the arc melting furnace, removing the surface oxide layer of the button sample, and reloading it into the arc melting furnace for suction casting treatment at a suction casting pressure of 1 to 10 Pa to obtain a coating scraper material.

9. The method for preparing the coating blade material according to claim 8, characterized in that: The specific process of removing the surface oxide layer of the button sample is: grinding the button sample with an angle grinder, a grinding wheel machine or sandpaper, and then using alcohol or acetone as a cleaning solvent to oscillate and clean the button sample in an ultrasonic wave for 5 to 10 minutes, and the power density of the ultrasonic wave is 0.5 to 1.5 W / cm 2 , frequency is 25~55Hz.